Homogeneous multigrid for HDG - Lu, Peipei; Rupp, Andreas; Kanschat, Guido (IMA journal of numerical analysis, 2022)
We introduce a multigrid method that is homogeneous in the sense that it uses the same hybridizable discontinuous Galerkin (HDG) discretization scheme for Poisson’s equation on all levels. In particular, we construct a stable injection operator and prove optimal convergence of the method under the assumption of elliptic regularity. Numerical experiments underline our analytical findings.